Development of Science Student Worksheets based on the Bio-Ecology of Cuttlefish (Sepia sp.) Cultivation to Improve Science Literacy for Junior High School Students - Lalu Muhammad Imam Husaini M. Nasir; Agil Al Idrus; Agus Ramdani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The development of the science student worksheet based on the bioecology of cuttlefish (Sepia sp.) cultivation is an effort to improve the scientific literacy skills of students at the coastal village school of East Lombok. The purpose of this research is to produce student worksheet that is feasible, practical, and effective in improving students' literacy skills. This research is research and development using Thiagarajan 4D development model which includes design, define, develop, and disseminate stages. The research subjects consisted of 1 SMP/MTs equivalent in East Lombok which were determined using purposive sampling technique. The instruments used include validation sheets, student and teacher response questionnaires, and scientific literacy assessment instruments. The feasibility and practicality data were analyzed using the percentage formula, and the effectiveness data were analyzed using the N-gain analysis. The results showed that 1) student worksheet science based on the bioecology of cuttlefish cultivation (Sepia.sp) was feasible to use with an average score of 73 for the content/material aspect, 73 for the language aspect, and 85 for the appearance aspect, 2) science student worksheet based on the bioecology of cuttlefish cultivation. (Sepia sp.) is practically used with an average percentage of student responses of 81% and teacher responses of 88%, 3) student worksheet science based on the bioecology of cuttlefish cultivation (Sepia.sp) is effective in improving students' scientific literacy skills with an average N value -gain of 0.5 in the medium category. Thus, it can be concluded that the science student worksheet based on the bioecology of cuttlefish (Sepia sp.) cultivation is feasible, practical, and effective to use in science learning as an effort to improve the scientific literacy of junior high school students in coastal village schools in East Lombok.